An aggregation-induced emission-active lysosome hijacker: Sabotaging lysosomes to boost photodynamic therapy efficacy and conquer tumor therapeutic resistance - Hang Zou; Pingping Wang; Zhihao Bai; Liping Liu; Jingtong Wang; Yanfang Cheng; Bairong He; Zujin Zhao; Lei Zheng (Materials Today Bio)
Therapeutic resistance is a major challenge in clinical cancer theranostics, often leading to treatment failure and increased patient mortality. Breaking this therapeutic deadlock, enhancing the efficacy of clinical treatments, and ultimately improving patient survival rates are both highly desirable and significantly challenging goals. Herein, we have developed a new fluorescent luminogen, QM-DMAC, which features aggregation-induced emission (AIE), and exceptional viscosity-responsive properties. The AIE-active QM-DMAC can specifically stain lysosomes in tumor cells, offering a high signal-to-noise ratio and enabling specific visualization of variations in lysosomal viscosity, such as those induced by inflammation or autophagy. Furthermore, QM-DMAC effectively generates reactive oxygen species (ROS) under white light irradiation, which precisely induces ROS-mediated lysosomal membrane permeabilization (LMP) and lysosome rupture. This ultimately causes severe cell damage and restores the sensitivity of tumor cells to radiotherapy and chemotherapy. Thus, QM-DMAC serves as a highly efficient lysosome-targeting photosensitizer and an excellent therapeutic sensitizer. This innovative “lysosome hijacking” strategy significantly maximizes the efficacy of photodynamic therapy, conquering therapeutic resistance and boosting the synergistic therapeutic effect when integrated with conventional radiotherapy or chemotherapy. It provides a novel approach to the design of theranostic agents for clinical cancer theranostics.